Beyond opinion living the faith that we defend - Zacharias, Ravi. (Nashville Thomas Nelson, 2007)
Addresses issues such as the validity of the Bible, the hypocrisy of its followers, and the need to make a new statement on faith, allowing Christians everywhere to simultaneously defend the faith and be transformed by it into people of compassion.
Includes bibliographical references (pages 343-360).
Keywords: Apologetics